Restricting energy intake of gestating sows with 50% alfalfa meal ration - G L Allee; B A Koch; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1977)
Gestating Yorkshire sows and gilts were randomly assigned to two dietary treatments immediately after a 25-day breeding season until females were brought to the farrowing house between 105-110th day of gestation. Sows and gilts fed the 50% alfalfa meal ration performed similarly to those fed the basal ration in regard to number of pigs farrowed, pigs weaned, and weights at birth, 14 and 28 days. The reduced caloric intake by sows fed 50% alfalfa meal was not detrimental to farrowing or reproductive performance.; Swine Day, Manhattan, KS, November 10, 1977
Keywords: Swine day; 1977; Kansas Agricultural Experiment Station contribution; no. 78-101-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 312; Swine; Sows; Gestation; Alfalfa meal ration; Farrowing; Basal ration